# -6-(-2x-y)=?

I believe it's:: 2x+y-6, because the negative in front of the parenthases means to switch the signs inside it, right? o.O

Edit:: Erm.. Maybe you should try some of these questions yourself? You're posting quite a few. They're not that hard if you think about it.

Nicole::Yes, it can be done. You just don't add or subtract the nubers with different variables. You leave it as it is, with the signs.

Miggie:: You aren't supposed to multiply the numbers inside the parenthases. After you change the signs, you take them away, leaving you with just a polynomial.
Jamel, 2x+y-6 . Pretty weird layout if I say so? What school gave you this crap?
know what..i think the operation can't be done.. basing from what i know, you cant add/ subtract nos. not having the same variables..but if its multiplication, or maybe division, then the operation can be done..
also, the one enclosed in a parenthesis is a binomial..
-6-(-2x-y)=0
-6(2x+y)=0
-12x-6y=0
-6y=12x+0
y=2x+0
OR
y=2x
So, when you do these, you have to get like terms on one side or the other. In this case, it's easiest to get the variables (x & y) on one side and numbers on the other. When you do this, both sides have to be equal...because this is an equation. What you do to one side, you have to do to the other (kind of like a balance scale...if you want to keep things blanced, you have to add weight or take it away on both sides at once).

-6 - (-2x-y)=

Add 6 to both side of the equal sign:

(-6+6) - (-2x-y)= +6, or -(-2x-y)=6. Now you can do some math. When you see a negative in front of a parenthetical statement, you are really seeing a -1. They just don't put that there. So, what you have is (using the asterisk * for "times")

-1 * (-2x-y) = 6, which equals 2x+y=6
(-1*-2x = +2x, and -1*-y = +y).
Now you have to decide if you are solving for x or y. Mostly they ask for x (but maybe this is the end of what your question is.you'll have to see what the book or assignment is looking for).

Solving for x, you have to get the x factor all on one side. So, with the equation 2x+y=6, you would want to move the y to the right side of the equals sign. You want it balanced, so you take y away from both sides.

2x+y - y = 6 - y

or

2x = 6-y

you can factor it further...divide each side by 2 (since you have 2x)

2x / 2 = x
6-y / 2 = 3-1/2 y

x=3- 1/2 y

Hope that makes sense...
4 